Penguatan Peran Komunitas Kesejahteraan Masyarakat Aceh Pesisir (KMAP) dalam Bidang Pendidikan, Ekonomi, Sosial Keagamaan, dan Politik di Aceh Tengah - Abdussyukur Abdussyukur; Ihsan Harun; Ansor Ansor; Ramadan Ramadan (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service aims to strengthen the Aceh Pesisir Community Welfare Community (KMAP)'s role in education, economy, society, and politics in Central Aceh amid the assumption that the immigrant community seems exclusive. The KMAP community works a lot and contributes in various fields. This service uses PAR (Participatory Action Research) method stages: Initial mapping of community inclusivity, building communication and trust with the community, determining the agenda for social change, participatory mapping, formulating problems, developing movement strategies, determining stakeholders, and formulating the possibility of planned success, taking action for change. At this stage, actions were carried out with small community groups in the fields of education, economy, socio-religious, and politics to strengthen the understanding of the inclusivity of the Aceh Coastal Community Welfare (KMAP) community group in Central Aceh. Finally, the program must be monitored and evaluated for the actions taken. Hierarchically, this service is carried out by interviews as a service database, conducting FGDs to increase understanding of the inclusiveness of community roles, community mentoring, and evaluation. As a result, the assisted community has a knowledge and common perception of the inclusive role in community development in education, economy, social religion, and politics.